2017
DOI: 10.3390/app7080770
|View full text |Cite
|
Sign up to set email alerts
|

Using a Molecular Dynamics Simulation to Investigate Asphalt Nano-Cracking under External Loading Conditions

Abstract: Recent research shows that macro-scale cracking in asphalt binder may originate from its intrinsic defects at the nano-scale. In this paper, a molecular dynamics (MD) simulation was conducted to evaluate the nucleation of natural defects in asphalt. The asphalt microstructure was modeled using an ensemble of three different types of molecules to represent a constituent species: asphaltenes, naphthene aromatics and saturates, where the weight proportion of 20:60:20 was used to create an asphalt-like ensemble of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Lu and Wang [17][18], Wang et al [19], and Xu and Wang [20] performed MD simulation to evaluate the mechanical properties of the bitumen-aggregate interface. MD simulation has also been applied to investigate the oxidative aging behaviours [21][22][23], diffusion and self-healing mechanisms [24][25][26], and micromechanical properties of bitumen [27][28][29]. These research efforts have produced important results for better understanding the physical, rheological, and thermodynamic properties of the real bitumen from a more fundamental perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Lu and Wang [17][18], Wang et al [19], and Xu and Wang [20] performed MD simulation to evaluate the mechanical properties of the bitumen-aggregate interface. MD simulation has also been applied to investigate the oxidative aging behaviours [21][22][23], diffusion and self-healing mechanisms [24][25][26], and micromechanical properties of bitumen [27][28][29]. These research efforts have produced important results for better understanding the physical, rheological, and thermodynamic properties of the real bitumen from a more fundamental perspective.…”
Section: Introductionmentioning
confidence: 99%
“…e stress state of the molecules in an asphalt binder model can be observed with the MD simulation; in addition, the process of molecules being pulled apart can also be observed by some visual software. Hou et al studied the initiation and propagation of crack in asphalt binder applying tension force on the molecular boundaries, and they found that the natural distribution of atoms at microscale would affect the intrinsic defects and further influence initiation and propagation of crack in the asphalt binder [58]. Nishimura and Miyazaki have used the MD simulation of a-Fe to investigate the mechanical behaviors under cyclic loading from a micro perspective.…”
Section: Nanocracking Behaviormentioning
confidence: 99%
“…MD simulation is conducted at microscale to analyze the main physical and mechanical properties of the asphalt binder based on the molecular interaction and local dynamics of particles. Some research studies in terms of MD application were investigated by us: the effect of wasting cooking oil on the macro-and microproperties of the asphalt binder, nanocracking under external loading conditions in the asphalt binder, and hardening effect on asphalt binder during the aging process as well as the effect of paraffin on the microproperties of the asphalt binder [49,[54][55][56][57][58]. In this study, we would like to describe the development status and some applications of this technology; some specific research of asphalt binder models is also described in this paper.…”
Section: Background and Introductionmentioning
confidence: 99%
“…If water continues to invade, it may further result in the loose failure of the structure (Guan et al, 2005;Yang, 2013). For these reasons, considering the remarkable progress in the traditional asphalt-based materials (Hou et al, 2017;Xu et al, 2018;Yang et al, 2020a,b), they still cannot achieve the long life of bridge deck pavement requirements.…”
Section: Introductionmentioning
confidence: 99%